Association between COVID-19 Vaccination and SARS-CoV-2 Infection among Household Contacts of Infected Individuals: A Prospective Household Study in England - Khitam Muhsen; Pauline A. Waight; Freja Kirsebom; Nick Andrews; Louise Letley; Charlotte M. Gower; Catriona Skarnes; Catherine Quinot; Rachel Lunt; Jamie Lopez Bernal; Stefan Flasche; Elizabeth Miller (Vaccines, 2024)
Background: We investigated whether COVID-19 vaccination reduced SARS-CoV-2 infection risk among adult household contacts of COVID-19 index cases during the Alpha, Delta, and Omicron waves in England. Methods: Between February 2021 and February 2022, SARS-CoV-2 RT-PCR nasal swabs were collected from COVID-19-confirmed index cases aged ≥20 years and their household contacts at enrolment and three and seven days thereafter. Generalized Estimating Equations models were fitted with SARS-CoV-2 positivity as the outcome and household contacts’ vaccination status as the main exposure while adjusting for confounders. Results: SARS-CoV-2 infection was confirmed in 238/472 household contacts (50.4%) aged ≥20 years. The adjusted relative risk (95% confidence interval) of infection in vaccinated versus unvaccinated household contacts was 0.50 (0.35–0.72) and 0.69 (0.53–0.90) for receipt of two doses 8–90 and >90 days ago, respectively, and 0.34 (0.23–0.50) for vaccination with three doses 8–151 days ago. Primary vaccination protected household contacts against infection during the Alpha and Delta waves, but only three doses protected during the Omicron wave. Vaccination with three doses in the index case independently reduced contacts’ infection risk: 0.45 (0.23–0.89). Conclusions: Vaccination of household contacts reduces their risk of infection under conditions of household exposure though, for Omicron, only after a booster dose.